Main factors and types of external labor migration of the population of in the Uzbekistan post-Soviet period (Eurasian Journal of Humanities and Social Sciences, 2023)
This article analyzes the main problems, factors and types of external labor migration of the population of the Republic of Uzbekistan in the post-Soviet period. In particular, inadequate government policy in terms of regulating the flow of labor migrants, social protection and creating conditions for their legal activities has caused migrants to become victims of trafficking